Associations of Bone Mineral Density with RANKL and Osteoprotegerin in Arab Postmenopausal Women: A Cross-Sectional Study - Osama E. Amer; Kaiser Wani; Mohammed G. A. Ansari; Abdullah M. Alnaami; Naji Aljohani; Saba Abdi; Syed D. Hussain; Nasser M. Al-Daghri; Majed S. Alokail (Medicina, 2022)
Background and objective: There is limited information as to the association of several key bone markers with bone mineral density (BMD) in understudied ethnic groups. This study investigated the relationship between circulating levels of osteoprotegerin (OPG) and receptor activator of nuclear factor kappa-Β ligand (RANKL) with BMD in Arab postmenopausal women. Materials and methods: In this cross-sectional study, a total of 617 Saudi postmenopausal women from the Osteoporosis Registry of the Chair for Biomarkers of Chronic Diseases were included. Anthropometric data, BMD, and biochemical data were retrieved from the registry. Participants were stratified into three groups based on T-score; n = 169 with osteoporosis, n = 282 with osteopenia, and n = 166 normal. Analysis of bone markers including RANKL, OPG, osteocalcin, and N-terminal telopeptide (NTx) was completed using commercially available bioassays. Results: The results suggested that OPG was significantly and positively correlated with age in the osteoporosis group (r = 0.29, p < 0.05), while it was inversely correlated with BMD femoral neck left (r = −0.56, p < 0.001) and BMD femoral neck right (r = −0.37, p < 0.05) in the same group. Moreover, RANKL showed a significant inverse correlation with NTx in the osteopenia group (r = −0.37, p < 0.05). Furthermore, the RANKL/OPG ratio had a positive and significant correlation with BMI (r = 0.34, p < 0.05), BMD femoral neck left (r = 0.36, p < 0.05) and BMD femoral neck right (r = 0.35, p < 0.05) in the osteopenia group. By contrast, it showed a significant inverse correlation with waist to hip ratio in the osteoporosis group (r = −0.38, p < 0.05). Multiple regression analysis showed that OPG contributes to BMD variations in the osteopenia group (p = 0.03). Conclusions: In conclusion, changes in circulating levels of RANKL and OPG might be a protective mechanism contrary to the increased bone loss in postmenopausal women.